Structural Breaks and the Expectations Hypothesis of the Term Structure: Some Empirical Evidence for the Philippines (2001-2017) - Tronzano, Marco (Asian Economic and Financial Review, 2018)
This paper extends the empirical investigation of Tronzano (2018b) applying a cointegration test allowing for a structural break in the long-run equilibrium relationship. In line with Tronzano (2018b) the null hypothesis of absence of cointegration is strongly rejected for all interest rates maturities, while a significant structural break is detected at the end of 2008. A decrease in risk premium components is documented after the 2008 structural break, while the “symmetry” restriction is only supported after this regime-shift. Overall, the policy prescriptions from this analysis are in line with those outlined in Tronzano (2018b) supporting a monetary policy strategy based on interest rate smoothing.